Effect of Dietary Supplementation of Nano Copper and Nano Zinc on Haematology and Biochemical Metabolites of Hariana Calves - P. Pandey, M. Kumar; V. Kumar; R.Kushwaha; S. Vaswani; A. Kumar; A. Singh; P.K Shukla; S. Prasad (Indian Journal of Animal Nutrition, 2024)
This study was conducted to determine the effect of dietary supplementation of nano copper (Cu) or nano zinc (Zn) alone or in combination on the haematology and blood metabolites in young calves. A total of 24 young Hariana calves were randomly assigned into four groups (6 calves per group) on body weight and age basis for a period of 120 days. Experimental calves were either received a basal diet devoid of supplemental Cu (control) or were supplemented with 10 ppm nano Cu (nanoCu10), 32 ppm nano Zn (nanoZn32) or combination of nano Cu and nano Zn (nanoCu10+nanoZn32). Blood was sampled at day 0, 30, 60, 90 and 120 post nano Cu and nano Zn supplementation for the determination of haematology attributes and blood metabolites. The mean plasma albumin concentrations were lower and plasma globulin concentrations was higher in nanoCu10+nanoZn32 group across 120 days study. However, there were no effect of treatments on the haematological attributes and most of the studied blood metabolites. Although, the treatment had significant effect on the plasma levels of Cu and Zn but no effect on plasma levels of other minerals was observed. Plasma Cu concentrations were higher in nanoCu10 and nanoCu10+nanoZn32 groups while plasma levels of Zn were higher in nanoZn32 and nanoCu10+nanoZn32 groups.